A MIF‐Derived Cyclopeptide that Inhibits MIF Binding and Atherogenic Signaling via the Chemokine Receptor CXCR2. (30th November 2020) - Krammer, Christine; Kontos, Christos; Dewor, Manfred; Hille, Kathleen; Dalla Volta, Beatrice; El Bounkari, Omar; Taş, Karin; Sinitski, Dzmitry; Brandhofer, Markus; Megens, Remco T. A.; Weber, Christian; Schultz, Joshua R.; et al.
Abstract: Macrophage migration inhibitory factor (MIF) is an inflammatory cytokine and atypical chemokine with a key role in inflammatory diseases including atherosclerosis. Key atherogenic functions of MIF are mediated by noncognate interaction with the chemokine receptor CXCR2. The MIF N‐like loop comprising the sequence 47–56 is an important structural determinant of the MIF/CXCR2 interface and MIF(47–56) blocks atherogenic MIF activities. However, the mechanism and critical structure–activity information within this sequence have remained elusive. Here, we show that MIF(47–56) directly binds to CXCR2 to compete with MIF receptor activation. By using alanine scanning, essential and dispensable residues were identified. Moreover, MIF(cyclo10), a designed cyclized variant of MIF(47–56), inhibited key inflammatory and atherogenic MIF activities in vitro and in vivo/ex vivo, and exhibited strongly improved resistance to proteolytic degradation in human plasma in vitro, thus suggesting that it could serve as a promising basis for MIF‐derived anti‐atherosclerotic peptides. Abstract : The specific targeting of the interaction between the atypical chemokine MIF and its receptor CXCR2, and its atherosclerosis‐promoting activity in a tailored peptide‐based approach is illustrated. Based on a structure–activity analysis of short N‐like loop‐derived MIF peptides, the cyclic MIF peptide analogue MIF(cyclo10) was identified as a promising candidate that blocks MIF/CXCR2 and counteracts MIF's inflammatory and pro‐atherogenic activity.